Healthcare Applications of pH-Sensitive Hydrogel-Based Devices: A Review - Hendi A (Dove Medical Press, 2020)
Asail Hendi,1 Muhammad Umair Hassan,2 Mohamed Elsherif,3 Bader Alqattan,4 Seongjun Park,5,6 Ali Kemal Yetisen,7 Haider Butt4 1School of Engineering, University of Birmingham, Birmingham B15 2TT, UK; 2Optoelectronics Research Lab, COMSATS University, Islamabad 45550, Pakistan; 3Department of Experimental Nuclear Physics, Nuclear Research Center, Egyptian Atomic Energy Authority, Cairo, Egypt; 4Department of Mechanical Engineering, Khalifa University, Abu Dhabi, United Arab Emirates; 5Department of Bio and Brain Engineering, Korea Advanced Institute of Science and Technology (KAIST), Daejeon 34141, Republic of Korea; 6KAIST Institute for Health Science and Technology (KIHST), Korea Advanced Institute of Science and Technology (KAIST), Daejeon 34141, Republic of Korea; 7Department of Chemical Engineering, Imperial College London, London SW7 2AZ, UKCorrespondence: Mohamed ElsherifDepartment of Experimental Nuclear Physics, Nuclear Research Center, Egyptian Atomic Energy Authority, Cairo, EgyptEmail elsherifmohamed109@gmail.comHaider ButtDepartment of Mechanical Engineering, Khalifa University, Abu Dhabi, United Arab EmiratesEmail haider.butt@ku.ac.aeAbstract: pH-sensitive hydrogels have been developed greatly over the past few years. This has been possible due to the synthesis of new hydrogel systems with increased sensitivity – a sensitivity of up to 10− 5 pH units has already been established. Recently, pH-sensitive hydrogels have shown to be very useful in biomedical applications, such as targeted cancer treatment and treatment of skin lesions. Prolonged drug release has been made available through the use of such hydrogels. The synthesis of pH-sensitive hydrogels is also quick and cost-effective. This review presents a background on the properties of pH-sensitive hydrogels and discusses some of the hydrogels with different sensitivity ranges and their possible applications. A range of synthesis processes have also been briefly introduced along with the fabrication of different structures such as microcantilevers and contact lenses.Keywords: pH-sensitive, sensors, hydrogels, biomedical applications, biocompatible